(untitled) (Research, Society and Development, 2023)
Objective: To identify the nutritional status of adolescents in school, food consumption at school and their level of physical activity of students ages 13 to 18 from the Ana Restrepo del Corral Educational Foundation (FEARC) in Bogotá during the year 2019-2020. Materials and Methods: The type of study was cross-sectional in a population of students ages 13 to 18 years, from the Ana Restrepo del Corral Educational Foundation (FEARC) in Bogotá, during the year 2019-2020. The sample was non-probabilistic for the convenience of 110 students. Results: Overweight, the risk of thinness and obesity; between overweight and obesity was found in 28.9% (n=44). The most frequent physical activities that were performed ≥3 times per week were walking/running, playing soccer and jumping in more than 30%. The most common foods consumed were processed sugars, products derived from cereals in more than 20%. Conclusion: Excess weight was higher than that found in the country, it was observed that males perform more physical activity than females,with consistent results in national and international surveys. The foods consumed are possibly not being eaten with the recommended frequency, which could affect their school performance and health.